Strangers in our midst: Immigration, social capital and segmented conflict - Griffiths, Clare E. (Criminology & criminal justice, 2022)
Putnam famously stated in his ‘hunkering down’ thesis that residents of diverse communities experiencing immigration retreat into their homes inhibiting the production of ‘social capital’. Immigration is therefore often posited to disrupt communities and positive social interaction, ultimately increasing tension and conflict between groups. Moving beyond Putnam’s simplistic account that immigration inevitably disrupts social capital, this article aims to instead show the complex features of civility and conflict that can co-exist among migrant and local communities. The research was based in a small working-class town in the North West of England that experienced the migration of Polish workers. Using a mixture of quantitative and qualitative methods, the key results show how new Polish migrants in particular demonstrate complex forms of social interaction displaying in-group hostility but out-group civility. Lenski’s notion of ‘status inconsistency’ is used to help explain why migrants with a high level of education but a low income are particularly mistrustful and intolerant of others.